Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's determine the function [tex]\( h(x) \)[/tex] which is the sum of the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex].
First, we have the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] given as:
[tex]\[ f(x) = x^2 - 3x + 5 \][/tex]
[tex]\[ g(x) = 2x^2 - 4x - 11 \][/tex]
To find [tex]\( h(x) \)[/tex], we simply add the two functions together:
[tex]\[ h(x) = f(x) + g(x) \][/tex]
Let’s add the expressions term by term:
1. For the [tex]\( x^2 \)[/tex] terms:
[tex]\[ x^2 + 2x^2 = 3x^2 \][/tex]
2. For the [tex]\( x \)[/tex] terms:
[tex]\[ -3x - 4x = -7x \][/tex]
3. For the constant terms:
[tex]\[ 5 - 11 = -6 \][/tex]
Putting these together, we get:
[tex]\[ h(x) = 3x^2 - 7x - 6 \][/tex]
So the correct form of [tex]\( h(x) \)[/tex] is:
[tex]\[ h(x) = 3x^2 - 7x - 6 \][/tex]
Among the given options, this matches with:
[tex]\[ h(x) = 3x^2 - 7x - 6 \][/tex]
Thus, the correct option is:
[tex]\[ \boxed{3x^2 - 7x - 6} \][/tex]
First, we have the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] given as:
[tex]\[ f(x) = x^2 - 3x + 5 \][/tex]
[tex]\[ g(x) = 2x^2 - 4x - 11 \][/tex]
To find [tex]\( h(x) \)[/tex], we simply add the two functions together:
[tex]\[ h(x) = f(x) + g(x) \][/tex]
Let’s add the expressions term by term:
1. For the [tex]\( x^2 \)[/tex] terms:
[tex]\[ x^2 + 2x^2 = 3x^2 \][/tex]
2. For the [tex]\( x \)[/tex] terms:
[tex]\[ -3x - 4x = -7x \][/tex]
3. For the constant terms:
[tex]\[ 5 - 11 = -6 \][/tex]
Putting these together, we get:
[tex]\[ h(x) = 3x^2 - 7x - 6 \][/tex]
So the correct form of [tex]\( h(x) \)[/tex] is:
[tex]\[ h(x) = 3x^2 - 7x - 6 \][/tex]
Among the given options, this matches with:
[tex]\[ h(x) = 3x^2 - 7x - 6 \][/tex]
Thus, the correct option is:
[tex]\[ \boxed{3x^2 - 7x - 6} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.